Interference between gait and cognitive tasks in a rehabilitating neurological population. Issue 4 (1st October 2000) - Haggard, Patrick; Cockburn, Janet; Cock, Josephine; Fordham, Claire; Wade, Derick
Abstract : OBJECTIVES: To quantify the extent of interference between gait and cognitive tasks after brain injury; to investigate whether such interference is common to various cognitive tasks, or confined to specific cognitive modules; to investigate whether such interference declines during recovery from brain injury. METHOD: Fifty participants were recruited from a neurological rehabilitation unit (33 people, 75% of sample); the stroke rehabilitation ward of an acute hospital (11 people, 20%); and a young disabled unit (six people, 5%). Measures of stride duration were taken in single task conditions, and in conjunction with each of four cognitive tasks. Outcome measures were dual task decrements in gait and in cognitive task performance. RESULTS: Overall, a 7% decrement in stride duration was recorded under dual task conditions compared with single task, with stride duration being significantly longer during simultaneous performance of each cognitive task. There was a 4% decrement on average in cognitive task performance under dual task conditions, with significant decrements being recorded for word generation while walking and paired associate monitoring while walking. A significant correlation ( r =0.45) was found between dual task decrements and scores on a standard measure of disability—the Barthel activities of daily living scale—but the correlation with 10 m walking time was not significant ( r =0.18). CONCLUSION: Interference between cognitive tasks and motor control activities such as gait is a problem in neurological rehabilitation settings. Interference between cognition and locomotor tasks may be important in assessing neurological patients' ability to function independently, and in designing therapies for both cognitive and motor rehabilitation.